2001
DOI: 10.1046/j.1439-0531.2001.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Embryos of Farm Animals

Abstract: This review contains two parts. The first part is devoted to the significant steps in cryopreservation of mammalian embryos with emphasis on cattle and sheep that serve as models of reference. These steps are: (1) shortening of cooling and warming processes; (2) addition and dilution of cryoprotectant in one step; (3) introduction of plastic straw as a freezing and dilution container; (4) the choice of ethylene glycol as the quite universal cryoprotectant because of its low toxicity and high permeability; (5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(68 citation statements)
references
References 82 publications
1
61
0
6
Order By: Relevance
“…Previous work with mature caprine oocytes indicated that the permeability of GLY was highly dependent on temperature, and at 20 °C [4] and 4 °C [16], this cryoprotectant has lower permeability than EG. Newton et al [18] compared the efficiency of four cryoprotectants (DMSO, propanediol, EG and GLY) in the cryopreservation of human ovarian tissue; they showed that EG had better results because it penetrated more quickly in the tissue, due probably to its lower molecular weight [50]. Based on the literature [12] and [16], EG was more effective at protecting cells during cryopreservation than GLY, perhaps due to its low toxicity and efficient permeability [51].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work with mature caprine oocytes indicated that the permeability of GLY was highly dependent on temperature, and at 20 °C [4] and 4 °C [16], this cryoprotectant has lower permeability than EG. Newton et al [18] compared the efficiency of four cryoprotectants (DMSO, propanediol, EG and GLY) in the cryopreservation of human ovarian tissue; they showed that EG had better results because it penetrated more quickly in the tissue, due probably to its lower molecular weight [50]. Based on the literature [12] and [16], EG was more effective at protecting cells during cryopreservation than GLY, perhaps due to its low toxicity and efficient permeability [51].…”
Section: Discussionmentioning
confidence: 99%
“…O glicerol possui peso molecular superior ao etilenoglicol (92,10 vs. 62,07 dáltons;Massip, 2001), esta característica confere ao glicerol baixa permeabilidade de membrana, o que leva a severos danos citoplasmáticos (Széll e Shelton, 1986). Diversos estudos têm demonstrado que a exposição do tecido ovariano ou de folículos pré-antrais ao glicerol, resulta em uma redução substancial na porcentagem de folículos viáveis em caprinos (Rodrigues et al, 2004) e ovinos (Santos et al, 2006).…”
Section: Methodsunclassified
“…In fact, vitrification is based on embryo manipula-tion into different carrier tools applied to minimize the volume and to submerge the sample quickly into liquid nitrogen, allowing an ultrafast freezing speed, which avoids ice crystal formation, thus eliminating its deleterious effects in the cell [157]. This technique combines the use of small volumes with high concentration of two or more cryoprotectants [158] and it can be more adapted to IVP embryos [149,159,160].…”
Section: Vitrificationmentioning
confidence: 99%